Alternative logistic concepts and their effect within the company and the supply chain - Farr, Richard; Holm, Sofia (VIVACE project, 2006)
This document presents findings from the simulation of a focused factory at Volvo Aero, Trollhättan. A series of experiments were carried out, aimed at testing a range of alternative logistic concepts. Each concept describes an approach to the control of workflow within the business, for the purpose of determining its effect within the company, and in the wider context of the supply chain.